Design of information system of traditional ethnomedicine Dayak Tribe in West Borneo - Ahmad Cahyono Adi; Dyan Puji Lestari; Elsa Elsa; Fiqrudina Sain Saputri (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
West Borneo is a province that has abundant biodiversity, based on data from the Central Statistics Agency. So far, education about medicinal plants is presented in the form of physical books. Unfortunately, the data and information about the types of medicinal plants have not been stored and documented properly. The absence of information technology in the form of a database that stores data about medicinal plants and their use causes information about these medicinal plants to be less known to the public. If allowed to continue, the government does not have a regional medicinal plant data center and the public is less familiar with and utilizes regional medicinal plant species, as a result, efforts to preserve medicinal plants as an ancestral medicinal culture will eventually become extinct. This research is the result of a literature study. Then a literature study or literature review is carried out with the data used sourced from scientific journal research and data related to existing research. Where the results of the literature study are the design of an ethnomedical information system in West Kalimantan. The results of a literature search found 85 species representing medicinal plants are still often used today by the Dayak community in West Borneo. The information system is expected to assist the community in knowing local medicinal plants and introducing ethnomedicine as well as a medium for learning local plants.Abstrak Kalimantan Barat merupakan provinsi yang memiliki keanekaragaman hayati yang melimpah, berdasarkan data Badan Pusat Statistik. Selama ini pendidikan tentang tanaman obat disajikan dalam bentuk buku fisik. Sayangnya, data dan informasi tentang jenis-jenis tanaman obat belum tersimpan dan terdokumentasi dengan baik. Belum adanya teknologi informasi berupa database yang menyimpan data tentang tanaman obat dan pemanfaatannya menyebabkan informasi tentang tanaman obat tersebut kurang diketahui masyarakat. Jika dibiarkan terus, pemerintah tidak memiliki pusat data tumbuhan obat daerah dan masyarakat kurang mengenal dan memanfaatkan jenis tumbuhan obat daerah, akibatnya upaya pelestarian tumbuhan obat sebagai budaya obat nenek moyang pada akhirnya akan punah. Penelitian ini merupakan hasil studi Metode penelitian ini adalah kualitatif untuk mengetahui pemanfaatan tumbuhan di Kalimantan Barat sebagai obat bagi masyarakat Dayak. Kemudian dilakukan studi kepustakaan atau literature review dengan data yang digunakan bersumber dari penelitian jurnal ilmiah dan data yang berkaitan dengan penelitian yang ada. Dimana hasil dari studi literatur adalah perancangan sistem informasi etnomedis di Kalimantan Barat. Hasil penelusuran literatur ditemukan 85 jenis tumbuhan obat yang masih sering dimanfaatkan oleh masyarakat Dayak di Kalimantan Barat hingga saat ini. Sistem informasi ini diharapkan dapat membantu masyarakat dalam mengenal tanaman obat lokal dan mengenalkan etnomedika serta sebagai media pembelajaran tanaman lokal.